The Role of Extracellular Vesicles in Efferocytosis - Panahi, Susan; Yazdi, Zohreh; Sanchouli, Mahboubeh; Sajadi, Fatemehsadat; Motavasselian, Fateme; Maghareh Abed, Hedyeh; Beygi, Zahra; Gheibihayat, Seyed M. (Mini Reviews in Medicinal Chemistry, 2024)
Efferocytosis is the physiological process of phagocytic clearance of apoptotic cells by both professional phagocytic cells, such as macrophages, and non-professional phagocytic cells, such as epithelial cells. This process is crucial for maintaining tissue homeostasis in normal physiology. Any defects in efferocytosis can lead to pathological consequences and result in inflammatory diseases. Extracellular vesicles (EVs), including exosomes, microvesicles (MVs), and apoptotic vesicles (ApoVs), play a crucial role in proper efferocytosis. These EVs can significantly impact efferocytosis by affecting the polarization of macrophages and impacting calreticulin (CRT), TAM receptors, and MFG-E8. With further knowledge of these effects, new treatment strategies can be proposed for many inflammatory diseases caused by efferocytosis disorders. This review article aims to investigate the role of EVs during efferocytosis and its potential clinical applications in inflammatory diseases.
Keywords: efferocytosis